Examining the Link Between Physical Activity and Cognitive Function: A Parallel Mediation Model of Health and Wellbeing Among Adolescents - Luan, Xi; Liu, Ji; Luo, Xin (Frontiers in Psychology, 2022)
Background Adolescents’ engagement in daily physical activity brings multiple benefits, including reduction in obesity, improvement of mental health, and enhancement of cognitive function (CF). While prior studies have examined the link between physical activity and cognitive function, little is known regarding the extent to which this relationship is shaped by health and wellbeing factors. This study examines how subjective wellbeing (SWB) and general health (GH) mediate the relationship between adolescents’ physical activity and cognitive function. Methods This study estimates a parallel structural equation model using the Program for International Student Assessment 2018 dataset. Specifically, a total of 63,228 15-year-old subjects in nine countries/economies satisfied the study inclusion criteria, including in Bulgaria, Georgia, Hong Kong, Ireland, Mexico, Panama, Serbia, Spain, and United Arab Emirates. Frequency of moderate physical activity (MPA, ≥3.0 Metabolic Equivalent Task) was reported weekly; SWB and GH were assessed using an internationally validated multi-item standardized questionnaire. SWB was measured by students’ self-evaluated satisfaction with their health, life, and schooling. GH was measured by students’ physical health and mental health status. Cognitive function (CF) was modeled as a latent function consisting of plausible values derived using item response theory on reading, mathematics, and science achievement tests. Results Findings indicated that increase in weekly MPA was positively associated with higher levels of SWB (p < .001), GH (p < .001), and CF (p < .001) among the study subjects. Parallel mediation analyses revealed that more frequent weekly MPA had relatively large direct effects (p < .001) on CF, and indirect effects channeling through improvements in SWB and GH were non-trivial (p < .001). Heterogeneity results showed that boosts to CF, associated with MPA, were larger for mathematics and science than for reading (p < .001). Conclusion This study used a large-scale international dataset to show that the positive relationship observed between MPA and CF among adolescents was robust, and that SWB and GH were two critical mediators through which physical activity positively bolster CF.